PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DALAM MENGGALI INFORMASI DARI DONGENG BINATANG (FABEL) PADA SISWA KELAS II SDN PARANG 4 KEDIRI (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Based on data obtained by researchers at SDN Parang 4, Banyakan sub-district, it was found the fact that there was a low level of activity and student learning outcomes in the material of digging information from animal tales (Fable).. In addition to this in everyday learning the teacher only conveys the material conventionally. Teachers only tend to give monotonous lectures and do not use learning models when carrying out learning in the classroom. Student activity is also very low, because when the teacher gives practice questions to students there are some students who just sit and don't seem eager to learn. The purpose of this research is toto find out the Application of the Role Playing Method for mimprove student activity and learning outcomes in dig up information from animal tales (Fables). The approach used is qualitative research with Classroom Action Research (CAR) design, with stages: 1) planning, 2) implementation, 3) observation, 4) reflection. This research is planned to last for 2 cycles, each cycle 2 meetings with thematic learning materials. Based on the results of research in the implementation of the first cycle of student learning completeness reached 50% and in the second cycle of student learning completeness increased to 91.60%. Based on the results of the study, it can be concluded that the Role Playing learning model can increase student activity and learning outcomes in extracting information from animal tales (fables) in class II SDN Parang 4, Banyakan District.